Regulation of the plasminogen activator activity and inflammatory environment via transforming growth factor-beta regulation of sperm in porcine uterine epithelial cells - Su-jin Kim; Hee-Tae Cheong; Choon-keun Park (The Korean Society of Animal Reproduction and Biotechnology, 2020)
The aims of the present study were to confirm that regulation of the PA and environment via TGF-β regulation of sperm by Percoll-separated in porcine uterine epithelial cells. And, it was performed to identify the cytokines (TGF-β1, 2 and 3, TGF-β receptor1 and 2; interleukin, IL-6, IL-8) and PA-related genes (urokinase-PA, uPA; tissue- PA, tPA; PA inhibitor, PAI; uPA-receptor, uPAR) by spermatozoa. The experiment used porcine uterus epithelial cells (pUECs) and uterine tissue epithelial cells, Boar sperm were separated by discontinuous Percoll density gradient (45/90%), and tissues were co-incubated with spermatozoa, followed by real-time PCR. PA activity was measured of sperm by discontinuous Percoll density gradient (45/90%) for 24 hours. To measure viability and acrosome damage of sperm double stained propidium iodide (PI) and SYBR- 14 or FITC-PNA were used. In results, binding ratio of Percoll-separated sperm was found no differences, but sperms isolated from 90% Percoll layer reduced PA activity (p < 0.05). when co-cultured sperm selected Percoll in porcine uterus tissues epithelial cells, 90% layer sperm increased TGF-β R1, contrastively tPA and PAI-1 in comparison with control (p < 0.05). 45% sperm was decreased the expression of uPA (p < 0.05). TGF-β decreased PA activity in the supernatant collected from pUECs (p < 0.05). Especially, The group including uPA, PAI-1 were induce sperm intact, while it was reduced in sperm damage when compared to control (p < 0.05). Also, there was no significant difference group of tPA and tPA+I in the dead sperm and acrosome damage compared to control. The expression of tPA and PAI showed a common response. Percoll-separated spermatozoa in 90% layer reduced tPA and IL-related gene mRNA expression. Thus, Percoll-sparated sperm in 90% layer show that it can suppress inflammation through increased expression of TGF-β and downregulation of PA and IL in epithelial cells compared to 45% layer Percoll.